Responses in organs, sperm, steroid hormones and CYP450 enzyme in male mice treated by quinestrol only or in conjunction with clarithromycin - Yu Ji; Yujie Wang; Yuhang Liu; Yutong Liu; Jiao Qin; Daohuan Yuan; Quansheng Liu (Scientific Reports)
Abstract Pest rodents persistently undermine crop yields and food security. Fertility control could be a viable alternative for managing rodent populations. This study investigates the antifertility effects of various concentrations of clarithromycin combined with 1.0 mg/kg quinestrol on male rodents to determine an effective contraceptive dose that minimizes quinestrol usage, addressing key concerns such as potential environmental residue, which may impact ecological balance, and poor palatability, which could reduce ingestion and limit the sterilant’s effectiveness. Male mice were divided into five groups and administered different doses of clarithromycin or clarithromycin and quinestrol for three consecutive days, while the control group received sunflower seed oil only. After seven days, organ weights, reproductive organ weights, sperm density, serum hormone levels, and CYP3A4 content in small intestinal and liver tissues were measured to assess persistent effects. Compared with the control group, all treatment groups had significant reductions in epididymal weight, seminal vesicle weight, and serum T and LH levels. Higher concentrations of clarithromycin (2 mg/kg and 10 mg/kg) significantly impacted reproductive metrics, including sperm density, organ weights, and serum LH and testosterone levels, though complete sterilization was not achieved, with more than 60 million cauda epididymal spermatozoa remaining. However, the combination demonstrated potential as an effective strategy for male fertility control. The combination of 2.0 mg/kg clarithromycin and quinestrol can mitigate organ enlargement seen with quinestrol alone. This combination also decreased total enzyme content, thereby diminishing quinestrol’s induction of CYP3A4, which may increase the sterilization effectiveness of the treatment.